Performance evaluation of a mechanical ventilation simulation model for diverse respiratory complications - Chetan Mahatme; Jayant Giri; Hamad A. Al-Lohedan; Faruq Mohammad; Neeraj Sunheriya; Rajkumar Chadge; Sathish T.; Pallavi Giri; Saurav Mallik; Manikandan Dhayalan (AIP Advances, 2024)
Medical life-saving techniques include mechanical ventilation. During the COVID-19 epidemic, the lack of inexpensive, precise, and accessible mechanical ventilation equipment was the biggest challenge. The global need exploded, especially in developing nations. Global researchers and engineers are developing inexpensive, portable medical ventilators. A simpler mechanical ventilator system with a realistic lungs model is simulated in this work. A systematic ventilation study is done using the dynamic simulation of the model. Simulation findings of various medical disorders are compared to standard data. The maximum lung pressure (Pmax) was 15.78 cmH2O for healthy lungs, 17.72 for cardiogenic pulmonary edema, 16.05 for pneumonia, 19.74 for acute respiratory distress syndrome (ARDS), 17.1 for AECOPD, 19.64 for asthma, and 15.09 for acute intracranial illnesses and head traumas. All were below 30 cmH2O, the average maximum pressure. The computed maximum tidal volume (TDVmax) is 0.5849 l, substantially lower than that of the healthy lungs (0.700 l). The pneumonia measurement was 0.4256 l, substantially lower than the typical 0.798 l. TDVmax was 0.3333 l for ARDS, lower than the usual 0.497 l. The computed TDVmax for AECOPD was 0.6084 l, lower than the normal 0.700 l. Asthma had a TDVmax of 0.4729 l, lower than the typical 0.798 l. In individuals with acute cerebral diseases and head traumas, TDVmax is 0.3511 l, lower than the typical 0.700 l. The results show the viability of the model as it performs accurately to the presented medical condition parameters. Further clinical trials are needed to assess the safety and reliability of the simulation model.